2020
DOI: 10.1111/ene.14632
|View full text |Cite
|
Sign up to set email alerts
|

SMART syndrome: retrospective review of a rare delayed complication of radiation

Abstract: Background SMART (stroke‐like migraine attacks after radiation therapy) is a rare, delayed complication of brain radiation. In this study, we wanted to review the spectrum of symptoms, neuroradiological findings, autoimmune status, and outcomes in SMART syndrome patients. Methods We conducted a retrospective cohort study of all consecutive adult patients (≥18 years) diagnosed with SMART syndrome at Mayo Clinic, Rochester between January 1995 and December 2018. Results We identified 25 unique patients with SMAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 24 publications
1
42
2
3
Order By: Relevance
“…18 Prior research in the setting of SMART syndrome has shown that the use of steroids was not significantly associated with worse clinical outcomes. 13,19 One study has proposed that to control seizure activity, a short course of highdose steroids can be considered for treatment. 2 However, whether steroid introduction can result in better clinical outcomes has still not been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Prior research in the setting of SMART syndrome has shown that the use of steroids was not significantly associated with worse clinical outcomes. 13,19 One study has proposed that to control seizure activity, a short course of highdose steroids can be considered for treatment. 2 However, whether steroid introduction can result in better clinical outcomes has still not been established.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly associated neurologic symptoms include hemiparesis (13/20), migraine-type headache (12/20), seizure (11/20), and speech impairment (9/20), findings consistent with those in prior studies. 2,13,14 Hemiparesis was the most prevalent remaining symptom at follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypotheses regarding pathophysiology for SMART include radiation-induced endothelial damage leading to impaired cerebrovascular autoregulation [3]. In the literature, the onset of symptoms ranges from one to 35 years after initial radiation [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of SMART syndrome remains poorly understood, some authors have speculated that deranged autoregulation caused by endothelial damage may be a causative factor. 6,7 In their review of radiotherapy-induced vasculopathy, Murphy et al specifically identified cerebrovascular accidents, moyamoya syndrome, vascular malformation, and hemorrhage as some of the principal vascular pathologies that take place years following cranial irradiation. 9,10 Given the high incidence of infarcts (not in an arterial distribution) demonstrated by Singh et al as well as the contrast enhancement found in most cases, it is thought that radiotherapy-induced vasculopathy plays a role in the pathogenesis of SMART syndrome.…”
Section: Pathophysiologymentioning
confidence: 99%